PENYULUHAN KEPADA GURU-GURU SEKOLAHDASAR TENTANG DETEKSI DINI GEJALAGANGGUAN JALAN NAPAS OBSTRUKTIF PADAANAK - Marpaung,SpPros.,PhD, Carolina Damayanti; Rahmadini, Enrita Dian; Dwidjayanti, Siti Chandra; Seftiana, Eka; Setyowati, Indrani; Dew, Ni Luh (Universitas Trisakti, 2025)
Obstructive airway disorders in children are common and hurt the child's development and quality of life. These disorders can also have long-term effects on children's health into adulthood. School teachers can be the first line of preventive efforts in children's health. Early detection of obstructive airway disorders is preventive care in children. This community service (PkM) aims to provide sufficient knowledge and skills to detect obstructive airway disorders in children. The training was given to 59 kindergarten and elementary school teachers at IPEKA BSD, which was divided into two topics: normal growth and disorders that occur in children and adolescents. The evaluation of activities showed a significant increase in knowledge of both topics. The low knowledge of breathing disorders can be increased significantly through this PkM activity. Good cooperation was also shown by the school, so that activities ran well and could be continued to become a sustainable routine activity.